KAJIAN PUSTAKA FAKTOR-FAKTOR YANG MEMPENGARUHI PERATAAN LABA SEBAGAI PRAKTIK MANAJEMEN LABA - Dhenta Agusti Widyantoro; Imroatul Lutfiana; Alfira Tiara Karisma; Aldalita Ajeng Rahmadani; Ardyan Firdausi Mustoffa (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
One of the valuation tools used to analyze financial statements is the profit earned by a company in order to be able to present good and appropriate company profits. The earnings management practice that companies tend to use is called